Power Relations in the Doctrine of Love for Ahlulbait: A Foucauldian Analysis of the Martajasah Community in Madura - Maulana, Wahyu; Mahzumi, Fikri (Islamic Review: Jurnal Riset dan Kajian Keislaman, 2025)
The doctrine of love for the ahlulbait in society always gives rise to discourse on power, domination, and even individual or small group gain. This study aims to discuss how the doctrine of love for the ahlulbait in Martajasah Madura is manifested, focusing on the power relations created through the perspective of Michel Foucault. This study employs a qualitative approach using data from observations and interviews. Interviews were conducted with Umar bin Abdullah Al-Hamid, Syarif Hidayatullah, Mohammad Yassir, and Umar Al-Faruq. This article finds that within the doctrine of love for the ahlulbait in Martajasah society, from the perspective of Michel Foucault's power relations, it plays a role in shaping social norms and supporting economic stability through religious practices. Additionally, love for the ahlulbait has a spiritual influence on individuals within the community. However, this doctrine also creates power dynamics between social control and resistance, resulting in an ongoing negotiation process among the research subjects. Doktrin cinta ahlulbait pada masyarakat selalu melahirkan sebuah wacana kekuasaan, dominasi, bahkan keuntungan individu atau kelompok kecil. Kajian ini ingin membahas tentang bagaimana doktrin cinta ahlulbait pada Martajasah Madura dengan menyoroti relasi-kuasa yang tercipta melalui perspektif Michel Foucault. Kajian ini menggunakan pendekatan kualitatif dengan menggunakan data dari hasil observasi dan wawancara. Wawancara dilakukan kepada Umar bin Abdullah Al-Hamid, Syarif Hidayatullah, Mohammad Yassir, Umar Al-Faruq. Artikel ini menemukan bahwa dalam doktrin cinta kepada ahlulbait pada masyarakat Martajasah, berdasarkan perspektif relasi-kuasa Michel Foucault, berperan dalam membentuk norma sosial dan mendukung stabilitas ekonomi melalui praktik keagamaan. Selain itu, cinta kepada ahlulbait memberikan pengaruh spiritual pada masyarakat secara individual. Namun doktrin tersebut juga menciptakan dinamika kekuasaan antara kontrol sosial, resistensi, sehingga di dalamnya terjadi proses negosiasi yang terus berlangsung pada subjek penelitian.